2007
DOI: 10.1158/1078-0432.ccr-06-1477
|View full text |Cite
|
Sign up to set email alerts
|

Serpin Peptidase Inhibitor Clade A Member 1 as a Potential Marker for Malignancy in Insulinomas

Abstract: Purpose: The biological behavior of insulinomas cannot be predicted based on histopathologic criteria in which the diagnosis of malignancy is confirmed by the presence of metastases. In this study, microarray and quantitative real-time reverse transcription-PCR were applied to identify differentially expressed genes between malignant and nonmalignant insulinomas to search for useful biomarkers to recognize the metastatic potential of insulinomas. Experimental Design: CodeLink human bioarrays were used to analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…[1][2][3][4] At present, only a few specific biomarkers for cutaneous SCC have been identified, including STAT3, 44 E-cadherin, 45 and matrix metalloproteinases 13, 46 12, 47 and 7. 6,48 SerpinA1 has been previously suggested as a biomarker for the progression of insulinoma 49 and thyroid cancer. 50 In this study, we introduced SerpinA1 as a potential biomarker for the progression of cutaneous SCCs combined with other biomarkers mentioned previously herein.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] At present, only a few specific biomarkers for cutaneous SCC have been identified, including STAT3, 44 E-cadherin, 45 and matrix metalloproteinases 13, 46 12, 47 and 7. 6,48 SerpinA1 has been previously suggested as a biomarker for the progression of insulinoma 49 and thyroid cancer. 50 In this study, we introduced SerpinA1 as a potential biomarker for the progression of cutaneous SCCs combined with other biomarkers mentioned previously herein.…”
Section: Discussionmentioning
confidence: 99%
“…This supports our experience with metastatic insulinoma with the vast majority of cases having high uptake on 68 Ga DOTATATE PET/CT. Further evidence of an association between SSTR expression and malignancy in insulinomas was identified in a quantitative PCR analysis of SSTR5 expression in a series of 16 primary insulinomas (four of which were plurihormonal) and two insulinoma metastases (de Sa et al 2006). Interestingly, SSTR5 mRNA was positively correlated with histological features of tumour aggressiveness, including large tumour diameter, proportion of cells with nuclear atypia, and plurihormonal secretion.…”
Section: :6mentioning
confidence: 91%
“…SSTR2 and SSTR3 induce cell apoptosis and SSTR1 and SSTR5 are related with cell cycle and affect cell proliferation and differentiation (Lamberts et al, 2002). Research has shown that SSTR5 is concerned strongly with infiltration of tumor and the expression of SSTR5 in insulinoma is lower markedly than normal tissue, indicating that SSTR5 has an intimately relationship with the proliferation of tumor (de Sa et al, 2006). Thus, therapeutic drugs effects depend on the expression of SSTRs in gallbladder cancer tissue.…”
Section: Discussionmentioning
confidence: 99%